2008
DOI: 10.1137/070692285
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Reconstruction of Piecewise Constant Images Using Nonsmooth Nonconvex Minimization

Abstract: Abstract. We consider the restoration of piecewise constant images where the number of the regions and their values are not fixed in advance, with a good difference of piecewise constant values between neighboring regions, from noisy data obtained at the output of a linear operator (e.g., a blurring kernel or a Radon transform). Thus we also address the generic problem of unsupervised segmentation in the context of linear inverse problems. The segmentation and the restoration tasks are solved jointly by minimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
171
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(177 citation statements)
references
References 51 publications
1
171
0
Order By: Relevance
“…The high quality of the minimization results for some functionals of the class F(·) is asserted in the works of Nikolova [17] and Bar et al [15], which successfully deals with both PWC or PWS signals corrupted with Impulsive and/or White noise by using edge-preserving regularization methods with non-smooth fidelity terms such as L 1 , Student's t-distribution, and Mestimators.…”
Section: Functions Typementioning
confidence: 98%
See 2 more Smart Citations
“…The high quality of the minimization results for some functionals of the class F(·) is asserted in the works of Nikolova [17] and Bar et al [15], which successfully deals with both PWC or PWS signals corrupted with Impulsive and/or White noise by using edge-preserving regularization methods with non-smooth fidelity terms such as L 1 , Student's t-distribution, and Mestimators.…”
Section: Functions Typementioning
confidence: 98%
“…Besides the trend-setting works of Geman and McClure [4] and Chipot et al [6], the practical effectiveness of non-convex functionals have also been shown in other studies. In signal/image denoising, the researches of Aubert et al [1], Nikolova [17] and Selesnick et al [18] illustrate by concrete examples the better performance of some non-convex functionals as compared to convex ones. Vese [19] shows the ability of several non-convex potentials to reconstruct signals, being particularly accurate at restoring edges and linear regions.…”
Section: Functions Typementioning
confidence: 99%
See 1 more Smart Citation
“…Some of these methods proceed first by selecting a non-convex penalty function that induces sparsity more strongly than the 1 norm, and second by developing non-convex optimization algorithms for the minimization of F ; for example, iterative reweighted least squares (IRLS) [38], [69], FOCUSS [37], [58], extensions thereof [47], [65], half-quadratic minimization [12], [34], graduated nonconvexity (GNC) [6], and its extensions [50]- [52], [54].…”
Section: B Related Work (Sparsity Penalized Least Squares)mentioning
confidence: 99%
“…We note that in [6], the proposed family of penalty functions are quadratic around the origin and that all a n are equal. On the other hand, the penalty functions we utilize in this work are non-differentiable at the origin as in [52], [54] (so as to promote sparsity) and the a n are not constrained to be equal.…”
Section: Introductionmentioning
confidence: 99%